2017
DOI: 10.1111/ecc.12739
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the provision of alcohol advice by clinicians to breast cancer patients

Abstract: Funding informationThis research did not receive any specific grant from funding agencies in the public, commercial or not-for-profit sectors.Interactions between clinicians and patients along the cancer trajectory provide an opportunity to deliver key messages regarding drinking behaviours and long-term health.This study aimed to explore the extent and nature of clinician-patient discussions regarding alcohol intake and cancer outcomes in the clinical breast cancer setting, using a qualitative research design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…While the cross-sectional nature of these data preclude the temporal ordering of breast cancer diagnosis and alcohol consumption levels, these results are consistent with previous research showing that some women continue to drink at risky levels or even increase their consumption after a breast cancer diagnosis [26]. Further, it has been found that health information about the alcohol-breast cancer link is not systematically provided to women receiving a diagnosis of breast cancer, with many completing treatment without any discussion of alcohol as a modifiable breast cancer risk factor [27]. Taken together, these findings make a case for providing tailored (discrete and nonstigmatizing) alcohol information to women who receive a breast cancer diagnosis, and women receiving breast cancer treatment, surveillance and supportive care.…”
Section: Discussionsupporting
confidence: 88%
“…While the cross-sectional nature of these data preclude the temporal ordering of breast cancer diagnosis and alcohol consumption levels, these results are consistent with previous research showing that some women continue to drink at risky levels or even increase their consumption after a breast cancer diagnosis [26]. Further, it has been found that health information about the alcohol-breast cancer link is not systematically provided to women receiving a diagnosis of breast cancer, with many completing treatment without any discussion of alcohol as a modifiable breast cancer risk factor [27]. Taken together, these findings make a case for providing tailored (discrete and nonstigmatizing) alcohol information to women who receive a breast cancer diagnosis, and women receiving breast cancer treatment, surveillance and supportive care.…”
Section: Discussionsupporting
confidence: 88%
“…There has been some exploration of the provision of alcohol advice to patients following a diagnosis of cancer (Simapivapan, Hodge, & Boltong, 2018;Williams, Beeken, Fisher, & Wardle, 2015). However, as prevention is the most cost-effective long-term strategy for cancer control, there is a need to educate and empower individuals prior to diagnosis, to make informed lifestyle choices to moderate their cancer risk (World Health Organisation, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%